Power Relation in Intercultural Marriage: Analysis of Power in Good Chinese Wife Memoir (2014) by Susan Blumberg-Kason - Adzanisyahra Tri Hardiyani; Safrina Noorman; Nia Nafisah (Passage, 2020)
The issue of power is prevalent in society today. Focusing on analyzing power issues in an intercultural marriage, Raven’s (2008) bases of power are applied in this research to investigate the matter. The issue is analyzed in a memoir by Susan Blumberg-Kason entitled Good Chinese Wife (2014) which tells about the conflicts in an intercultural marriage. This research aims to identify the types of power proposed by Raven (2008) used by the husband, to exercise his power over his wife and how it is exercised. The only visible types of power in the memoir are expert power, referent power, and coercive power. In addition, the conflict that is caused by superiority becomes the main conflict in their marriage life since it occurs in every three types of power. The husband can exercise his power over his wife because he takes advantage of her love for the husband’s culture, which in this case is Chinese culture. The results of the study show that power can be constructed in the name of love.  Keywords: culture; intercultural marriage; memoir; power; superiority.